Register Variation of PKK RT 03 Kendung Rejo Surabaya - Erika Alisia (Humanitatis : Journal of Language and Literature, 2023)
This study proposes to find the various and the meaning of registers, and the kinds of social classes in the community. The register is defined as the language variation that is used by the community in their communication. The community was the PKK community in RT 003 RW 008 Kendung Rejo. Member of PKK community as subjects to analyse. This study is a qualitative ethnography that focuses on the community within its natural context and the participants’ beliefs, behaviour, value etc. It was performed by conversation and chats. The data was collected offline gathering at RT’s building and through online Whatsapp group chats. As a result, the frequency of registers obtained offline is 13 registers, and online is 12 registers. In offline, 13 registers are Mars PKK, KSK, Akta, Pendataan, KTP, Lotre, Doorprize, Dawis, Bumantik, Buku Ijo, Buku Ungu, Jentik, and Abate. While, online mentioned 12 register sent by member in Whatsapp group such as Virus PMK, Ngelapak, MBR, Sapling, Sensus, Infak, Ta’mir, Imunisasi, Balita, Timbang, KB IUD, and Implan. Mostly in social class, the information was delivered by the head of RT 03 and the head of Dasawisma. Different members’ social classes showed different registers and how important the information conveyed.